Plasma cell neoplasm with initial presentation as an ovarian mass: a rare case report. (9th November 2022) - Shirai, S; Wang, W; Guo, T; Buryanek, J; Chen, L
Abstract: Introduction/Objective: Plasmacytoma is a discrete, solitary mass of neoplastic plasma cells. Extramedullary plasmacytoma (EMP) is a rare entity arising in tissues other than bone and it constitutes about 1% of all plasma cell neoplasms. Most cases of reported EMPs are in the upper aerodigestive tract ( 80%). We present a very rare case with the initial presentation as an ovarian mass with metastasis into the peritoneal and pleural cavity. Methods/Case Report: This is a 66-year-old female who presented with generalized abdominal pain, unexpected weight loss, and occasional fever and night sweats. Computed tomography (CT) scan of abdomen and pelvis showed an extensive metastatic disease including bilateral cardiophrenic angle lymphadenopathy, peritoneal spread encasing the bowel loops, bladder, and uterus as well as moderate right pleural effusion. The positron emission tomography (PET)-CT showed an ill-defined soft tissue density in the pelvis with hypermetabolism. The pelvic ultrasound showed a 2.6 x 2.2 x 1.1 cm hypoechoic mass in the left adnexa. The patient's serum cancer antigen (CA-125) was elevated at 123 U/mL and the post-thoracentesis chest x-ray was unremarkable with no acute osseous abnormalities. Other clinical data were not available. Results (if a Case Study enter NA): Cytopathologic evaluation of the pleural fluid showed abundant atypical cells with eccentrically located nuclei, scant to moderate cytoplasm with a paranuclear hof, frequent binucleation and mitoses. The cells ranged in size from small to large. Further immunohistochemical (IHC) analysis on the cell block showed that the tumor cells diffusely positive for CD138 and lambda light chain and negative for MOC31, BerEP4, calretinin, D2-40, WT1, HHV8, ALK1, and EBER in situ hybridization (ISH). The biopsy of the left adnexal mass showed a diffuse proliferation of tumor cells with frequent mitotic figures. The IHC analysis on the biopsy specimen showed tumor cells positive for CD79a and CD56 (weak) and negative for CD20 and PAX5. Kappa/lambda ISH analysis confirmed lambda light chain restriction of the tumor cells. These morphological and immunophenotypic features were consistent with plasma cell neoplasm. Conclusion: The ovary is an unusual location to be involved by plasma cell neoplasm. We use this case to remind the pathologists and clinicians that ovarian plasmacytoma can be the initial presentation of the plasma cell neoplasm, although rare, and to aid the patients to receive an appropriate treatment. A thorough workup is needed to make an accurate diagnosis of this entity.